Hubungan Kesehatan Mental Dengan Motivasi Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam Kelas IX SMP Al-Azhar 3 Bandar Lampung - Pramudya Hesti Permadi; Harjoni Harjoni; Nur Asiah; A. Fatoni (Journal on Education, 2024)
Mental health is very necessary for someone in all their life activities, especially students who are currently studying. Mental health is crucial for the development of students, especially students in their teens. To achieve maximum motivation to learn, high mental health is required, however, if students are not mentally healthy, this is indicated by several things that happen to them, such as lack of enthusiasm for learning, lethargy, lack of enthusiasm, stress due to mental pressure, stress and so on. The research method used is quantitative research using field research with a correlation approach. The data collection technique in this research is using questionnaires and documentation. This research was conducted at Al-Azhar 3 Middle School in Bandar Lampung, namely regarding mental health and learning motivation. The results of hypothesis testing with Pearson Correlation obtained a value of 0.825 with a significance value of 0.000 (p-value < a = 0.05), which means a significant relationship exists between mental health and student learning motivation in Islamic Religious Education subjects in class IX of junior high school. Al-Azhar 3 Bandar Lampung. It can be concluded that having healthy mental health will tend to increase high learning motivation, on the other hand, students with unhealthy mental health will tend to have low learning motivation.